The sunflower transcription factor HaWRKY76 confers drought and flood tolerance to Arabidopsis thaliana plants without yield penalty - Raineri, Jesica (2015)
Key message: Arabidopsis transgenic plants expressing the sunflower transcription factor HaWRKY76 exhibit increased yield and tolerance to drought and flood stresses. The genetic construct containing HaWRKY76 is proposed as a potential biotechnological tool to improve crops. Abstract: Water deficit and water excess are abiotic stress factors that seriously affect crops worldwide. To increase the tolerance to such stresses without causing yield penalty constitutes a major goal for biotechnologists. In this survey, we report that HaWRKY76, a divergent sunflower WRKY transcription factor, is able to confer both dehydration and submergence tolerance to Arabidopsis transgenic plants without yield penalty. The expression pattern of HaWRKY76 was analyzed in plants grown in standard conditions and under different watering regimes indicating a regulation by water availability. The corresponding cDNA was isolated and cloned under the control of a constitutive promoter and Arabidopsis plants were transformed with this construct. These transgenic plants presented higher biomass, seed production and sucrose content than controls in standard growth conditions. Moreover, they exhibited tolerance to mild drought or flood (complete submergence/waterlogging) stresses as well as the same or increased yield, depending on the stress severity and plant developmental stage, compared with controls. Drought tolerance occurred via an ABA-independent mechanism and induction of stomatal closure. Submergence tolerance can be explained by the carbohydrate (sucrose and starch) preservation achieved through the repression of fermentation pathways. Higher cell membrane stability and chlorenchyma maintenance could be the nexus between tolerance responses in front of both stresses. Altogether, the obtained results indicated that HaWRKY76 can be a potential biotechnological tool to improve crops yield as well as drought and flood tolerances.